Family income and exposure to norovirus in childhood: Findings from the UK Millennium Cohort Study - Mara Violato; David Taylor-Robinson; Daniel Hungerford; Alastair Gray; Sarah O'Brien; Miren Iturriza-Gomara (Elsevier, 2019)
Children from low income families are at greater risk of poorer health outcomes than their wealthier peers. Hospital admissions for children with gastroenteritis increase as deprivation increases. Noroviruses are responsible for 47-96% of outbreaks of acute paediatric gastroenteritis, and 5-36% of sporadic cases worldwide. However, evidence on the relationship between family income and childhood exposure to norovirus is still limited, with published studies pointing to conflicting results. This study explored the relationship between family income and early childhood exposure to norovirus in the United Kingdom using data from the Millennium Cohort Study linked to serological data. Exposure to norovirus was measured by the level of human norovirus-specific antibodies (titres) obtained from oral fluid samples collected from 5962 pre-school age UK children and tested for Norovirus-specific Immunoglobulin G (IgG). Multivariable linear and quantile regression analyses were conducted to investigate the extent to which family income was associated with child norovirus exposure, and to explore the potential mechanisms through which income might translate into norovirus exposure. Higher norovirus-specific IgG titres were associated with higher family income, but the relationship weakened after controlling for potential mediating factors, mainly increased opportunities for person-to-person contacts, such as formal childcare arrangements. This study provides novel evidence that can help inform and prioritise policy interventions (e.g. vaccination) and health promotion programmes to reduce child health inequalities in the area of gastrointestinal infections. Keywords: UK, Child health inequalities, Income gradient, Norovirus exposure, Immunoglobulin G, Regression analysis